Powrót do prawa powielaczowego? Rzecz o wytycznych Ministra Zdrowia z 30 sierpnia 2024 roku - Szczucki, Krzysztof; Olszówka, Marcin (PRAWO i WIĘŹ, 2025)
Abstract According to the 1997 Constitution of the Republic of Poland, legal norms may be established either through an act of universally binding law (which may address anyone) or through an act of internally binding law (which may address only entities organizationally subordinate to the issuing authority). Guidelines cannot contain norms of universally binding law. The detailed regulation of the sources of law in the 1997 Constitution was intended to prevent a return to the situation from the communist era (PRL), when various state bodies, through various informal instruments, effectively created universally binding laws, often modifying statutes – a phenomenon referred to as „mimeograph law”. The guidelines issued by the Minister of Health on 30 August 2024 concerning abortion exhibit many features characteristic of mimeograph law: a lack of legal basis and promulgation; the modification and denial of statutory provisions; and a descriptive formulation (rather than the form of legal provisions). This obscures the normative novelty introduced by the Minister’s guidelines of 30 August 2024.